2021
DOI: 10.1111/famp.12740
|View full text |Cite
|
Sign up to set email alerts
|

Parental burnout during the COVID‐19 pandemic

Abstract: Increased and long‐term parental stress related to one's parental role can lead to parental burnout. In the early phase of the COVID‐19 pandemic, families experienced intensified pressure due to the government‐initiated contact restrictions applied to prevent the spread of the virus in the population. This study investigates the risk factors and predictors of parental burnout in a large sample of parents (N = 1488) during the COVID‐19 pandemic in Norway. Demographic and psychosocial factors were assessed at tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 45 publications
5
21
0
1
Order By: Relevance
“…It is important to note that parental age was negatively associated with parental burnout in this sample during the second year of the COVID-19 pandemic. This finding is consistent with those from studies of parenting in the early stages of the pandemic ( Skjerdingstad et al, 2021 ; Sorkkila & Aunola, 2021 ; Woine et al, 2022 ). It could be that older age as a parent offered certain protective factors, such as increased parenting experience ( Woine et al, 2022 ), that helped parents cope with parenting stressors as pandemic-related changes continued into the second year.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…It is important to note that parental age was negatively associated with parental burnout in this sample during the second year of the COVID-19 pandemic. This finding is consistent with those from studies of parenting in the early stages of the pandemic ( Skjerdingstad et al, 2021 ; Sorkkila & Aunola, 2021 ; Woine et al, 2022 ). It could be that older age as a parent offered certain protective factors, such as increased parenting experience ( Woine et al, 2022 ), that helped parents cope with parenting stressors as pandemic-related changes continued into the second year.…”
Section: Discussionsupporting
confidence: 91%
“…Likewise, parents reported they felt more stressed and burned out in their role as a parent ( Le Vigouroux et al, 2022b ). This finding also lends support to other parenting studies conducted during the pandemic, which similarly found parental stress predicted parental burnout ( Skjerdingstad et al, 2021 ). The finding that parents experienced parenting demands and stressors during the pandemic that exceeded their resources and contributed to parental burnout is also consistent with family stress theory ( Patterson, 2002 ).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Another important phenomenon during the COVID-19 outbreak is the so-called parental-related exhaustion, defined as feelings of being overextended and depleted of one’s emotional and physical resources. Exhaustion is a key aspect of parental burnout, which results from prolonged exposure to parental stress, which influences the psychological wellbeing of children [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%